Epithelioid hemangioendothelioma prognosis and outcome: report of two challenging cases - Parviz Mardani; Zahra Hashempour; Reza Shahriarirad; Armin Amirian (Journal of Cardiothoracic Surgery)
Abstract Background Epithelioid hemangioendothelioma (EHE) is an uncommon vascular malignancy characterized by an unpredictable clinical course and a high potential for recurrence and metastasis. The lack of standard treatment guidelines, coupled with the tumor’s inconsistent response to available treatments, complicates the management of EHE and leads to widely varying patient prognoses. Case presentation We report two cases of EHE with distinct presentations reflecting the site of involvement. The first case involved a patient with pulmonary EHE who initially benefited from complete surgical resection of the tumor after chemotherapy. However, the patient experienced two episodes of metastatic recurrence, resistant to further surgical and chemotherapeutic interventions, ultimately leading to the patient’s death forty-two months after the diagnosis. The second case presented with a mediastinal EHE involving the para-esophageal area. Partial tumor resection was achieved but postoperative imaging revealed extensive metastasis and pleural effusion. Despite additional treatments, the disease progressed rapidly, and the patient passed away fourteen months following the initial diagnosis. Conclusions The optimal therapeutic approach for EHE remains controversial due to its unpredictable treatment response, particularly in recurrent or metastatic cases. Therapeutic investigations are needed to establish evidence-based guidelines that can address treatment challenges and ensure the best possible outcome for each patient.